Research on Lemongrass Oil Extraction Technology (Hydrodistillation, Microwave-Assisted Hydrodistillation) - Thien Hien Tran; Duy Chinh Nguyen; Thuong Nhan Nguyen Phu; Van Thi Thanh Ho; Dai Viet Nguyen Vo; Long Giang Bach; Trinh Duy Nguyen (Indonesian Journal of Chemistry, 2019)
Microwave-assisted hydro-distillation (MAHD) is preferred to traditional extraction methods due to shorter extraction time, the inability of volatile components to be damaged or decomposed which in turn improve the efficiency and quality of essential oils. In this research, we investigated the parameters that affect the extraction of lemongrass oil process by MAHD method and compare with those of hydro-distillation (HD) method. Four parameters were identified which are: raw material size, raw material to water ratio, extraction time and microwave power. The results show that the optimum condition for determining the lemongrass essential oil content is 20 mm in the 90 min extraction time with a microwave power of 450 W at raw material to water ratio of 1:3 (g/mL). When compared to the HD method, we found that the yield lemongrass oil of MAHD method is 0.35% on 90 min and the yield of HD method is 0.2% on 360 min. The quality of oil samples at different extraction method was evaluated by determining their chemical constituents through GC-MS. The highest identified component is Citral with 93.28% for MAHD, while the HD was 83.85%. Therefore, MAHD method is highly efficient and shorten the time needed for the extraction of essential oils.